2014
DOI: 10.1063/1.4896624
|View full text |Cite
|
Sign up to set email alerts
|

Thermally driven analog of the Barkhausen effect at the metal-insulator transition in vanadium dioxide

Abstract: Abstract:The physics of the metal-insulator transition (MIT) in vanadium dioxide remains a subject of intense interest. Because of the complicating effects of elastic strain on the phase transition, there is interest in comparatively strain-free means of examining VO 2 material properties. We report contact-free, low-strain studies of the MIT through an inductive bridge approach sensitive to the magnetic response of VO 2 powder. Rather than observing the expected step-like change in susceptibility at the trans… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The Barkhausen effect has been a powerful tool to characterize magnetic and ferroelectric materials [24][25][26][27], and it has also attracted growing interest as an example of complex dynamical systems displaying dimensiondependent scaling behavior [22]. Given the ubiquitous presence of the Barkhausen effect in magnetic phase transition [24][25][26][27][28][29], only a limited number of research has revealed Barkhausen physics in thermally-driven first-order phase transition in non-magnetic materials [30][31][32][33][34][35], and none of such transition has been observed in van der Waals layered crystals.…”
Section: Introductionmentioning
confidence: 99%
“…The Barkhausen effect has been a powerful tool to characterize magnetic and ferroelectric materials [24][25][26][27], and it has also attracted growing interest as an example of complex dynamical systems displaying dimensiondependent scaling behavior [22]. Given the ubiquitous presence of the Barkhausen effect in magnetic phase transition [24][25][26][27][28][29], only a limited number of research has revealed Barkhausen physics in thermally-driven first-order phase transition in non-magnetic materials [30][31][32][33][34][35], and none of such transition has been observed in van der Waals layered crystals.…”
Section: Introductionmentioning
confidence: 99%